Conditions for a New-Reconceptualization of Social Work in Chile, Latin America and the Caribbean - Vivero-Arriagada, Luis Alberto (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
This paper aims, at a preliminary analysis of the material and subjective conditions supporting, a redefinition of social work. As an assumption it is proposed that Social Work, in the current historical and political context, is strongly influenced by neoliberal ideology. Neoliberalism has been hegemonic in Chile after its imposition by the civil-military dictatorship, along with the 'Chicago Boys', as its organic intellectuals. A disciplinary discussion is required on the material conditions that account for worrying gaps of inequality and exclusion as a consequence of the ideo-political matrix, beyond the strictly methodological and instrumental issues. This is a disciplinary reorientation in the field of its functionality, which we have called New-Reconceptualization. Reflections presented here come from the results of a qualitative investigation.